Original articleUltrastructure of meningiomas: autophagy is involved in the pathogenesis of “intranuclear vacuoles” - Jaskólski, Dariusz; Papierz, Tomasz; Liberski, Paweł P.; Sikorska, Beata (Folia Neuropathologica, 2012)
We report here common ultrastructural findings in a short list of meningiomas. At the lower power magnification, a tumour consisted of elongated or round cells and innumerable cellular processes connected with diverse intercellular junctions. Nuclei presented no specific features, nucleoli were infrequently seen and heterochromatin was clumped beneath the nuclear membranes. In a case of clear cell meningioma, cells were of watery cytoplasm. Occasionally, immobile cilia, completely ensheathed by the cytoplasm and anchored by blepharoplasts were seen; as we did not encounter those rare cilia in cross-sections, no further insight into their inner microtubular-doublet structure was possible. The cytoplasm of the cells and the processes were filled with the intermediate filaments. In the intercellular space, collagen fibrils and electron-dense material was occasionally observed. The majority of the tumour samples were filled with processes. Several types of junctional complexes were observed. The most frequent were desmosomes and in the proper plane of section their whole pentalaminar structure was readily discernible. However, robust tonofilaments, as seen in epithelial neoplasms, were not observed. Those desmosomal junctions were either completely symmetric or asymmetric, but the exact symmetry could not be judged without the assistance of a goniometer. Some junctional complexes were more elaborate, with desmosomal junctions separated by a tight apposition of membranes, which suggests tight junctions. “Intranuclear vacuoles” well-visible even at low power were defined as indentation of the cytoplasm into the nucleus. Within these vacuoles, autophagic vacuoles and lysosomal bodies were seen, suggesting an active macroautophagy process. In 2 cases, severe lipidization of meningioma cell cytoplasm was observed. In a case of anaplastic meningioma, a mitotic figure was found. In another case, empty rectangular spaces in the cytoplasm, suggestive of pre-existing crystalloid structures, were seen.